HYSTERESIS IN POST-KEYNESIAN MONETARY THEORY - Chytil, Zdenek; Maslo, Lukas (European Scientific Journal, ESJ, 2015)
This paper focuses on research in Post-Keynesian economics of (non)equilibrium applied to monetary policy. The authors show by an amended New Consensus model that a case they call â€œLavoieâ€™sâ€ hysteresis is substantially different from Setterfieldâ€™s (1998a) conception, despite some common features. The paper claims that in spite of presence of irreversibility and short-run and long-run path-dependence in both systems, there are some fundamental differences. Drawing upon the Kaldor - Setterfieldâ€™s definition of determinate outcome, the authors argue that â€œLavoieâ€™sâ€ (2008) hysteresis in the natural rate is a locally-stable-multiple-equilibria case and they regard, in reference to Setterfieldâ€™s concepts of deep endogeneity and adjustment asymmetries, â€œLavoieâ€™sâ€ hysteresis a conceptualization of historical time at a lower level than Setterfieldâ€™s hysteresis. This paper states that Setterfieldâ€™s (2008) references to his theory of hysteresis as a general theory, of which the traditional equilibrium is just a special case, might be applied to â€œLavoieâ€™sâ€ hysteresis only on the condition that differences between â€œSetterfieldâ€™sâ€ and â€œLavoieâ€™sâ€ thresholds were neglected. The final conclusion is drawn by the authors that presence of â€œLavoieâ€™sâ€ hysteresis is a sufficient condition for the limited long-run money neutrality to arise.